Brain-targeted delivery shuttled by black phosphorus nanostructure to treat Parkinson's disease. (November 2020) - Xiong, Sha; Li, Zhongjun; Liu, Yao; Wang, Qun; Luo, Jingshan; Chen, Xiaojia; Xie, Zhongjian; Zhang, Yuan; Zhang, Han; Chen, Tongkai
Abstract: The treatment of Parkinson's disease (PD) is hampered by the blood-brain barrier (BBB). As such, there is an urgent need for the development of a novel nanoplatform capable of penetrating the BBB in order to effectively treat PD. In the present study, we utilized black phosphorus nanosheets (BP) containing the brain-targeting ligand lactoferrin (Lf) and loaded with Paeoniflorin (Pae) to obtain Lf-BP-Pae. Through an effective photo-thermal effect, these Lf-BP-Pae particles were capable of traversing the BBB and effectively treating PD in a targeted manner. Importantly, this BP-based nanoplatform was capable of achieving satisfactory biocompatibility and biosafety with excellent anti-Parkinsonian efficacy, making it ideal for clinical applications. Graphical abstract: The combination of brain-targeted black phosphorus nanostructure and near-infrared irradiation could increase BBB permeability in vitro and in vivo, thereby offering significant anti-Parkinsonian efficacy. Image 1